Oriented Two‐Dimensional Covalent Organic Framework Membranes with High Ion Flux and Smart Gating Nanofluidic Transport - Cao, Li; Liu, Xiaowei; Shinde, Digambar B.; Chen, Cailing; Chen, I‐Chun; Li, Zhen; Zhou, Zongyao; Yang, Zhongyu; Han, Yu; Lai, Zhiping (Angewandte Chemie International Edition, 2022)
Nanofluidic ion transport holds high promise in bio‐sensing and energy conversion applications. However, smart nanofluidic devices with high ion flux and modulable ion transport capabilities remain to be realised. Herein, we demonstrate smart nanofluidic devices based on oriented two‐dimensional covalent organic framework (2D COF) membranes with vertically aligned nanochannel arrays that achieved a 2–3 orders of magnitude higher ion flux compared with that of conventional single‐channel nanofluidic devices. The surface‐charge‐governed ion conductance is dominant for electrolyte concentration up to 0.01 M. Moreover, owing to the customisable pH‐responsivity of imine and phenol hydroxyl groups, the COF‐DT membranes attained an actively modulable ion transport with a high pH‐gating on/off ratio of ≈100. The customisable structure and rich chemistry of COF materials will offer a promising platform for manufacturing nanofluidic devices with modifiable ion/molecular transport features. We report smart nanofluidic devices based on oriented two‐dimensional covalent organic framework membranes that offer vertically aligned nanofluidic channel arrays, leading to an ultrahigh ion flux and pH‐gating nanofluidic transport.